226. Multidrug Resistant Polymicrobial Gram-negative Bacteremia in Hematologic Cancer Patients with Febrile Neutropenia at the Uganda Cancer Institute. (4th December 2021) - Lubwama, Margaret; Bwanga, Freddie; Kateete, David; Adams, Scott; Namubiru, Betty; Nabiryo, Barbara; Orem, Jackson; Phipps, Warren
Abstract: Background: Bloodstream infections (BSI) are associated with significant mortality in hematologic cancer patients with febrile neutropenia. Poor clinical outcomes are associated with presence of multidrug resistant (MDR) organisms and polymicrobial infections. We sought to determine antimicrobial resistance and outcomes of polymicrobial bloodstream infections in hematologic cancer patients with febrile neutropenic episodes (FNEs) at the Uganda Cancer Institute. Methods: Blood drawn from participants during an FNE (fever ≥ 37.5°C and neutrophil count ≤ 1000 cells/µL) was cultured in the BACTEC 9120 blood culture system. Bacteria from positive cultures were identified biochemically. Antimicrobial susceptibility testing was performed with the disc diffusion method. Participants were followed for 30 days from first FNE onset for death from any cause. Cox regression was used to estimate hazard ratios (HR) and 95% confidence intervals (95%). Results: Six hundred and twenty-nine participants were followed for FNE. Two hundred and twenty-eight FNEs in 159 participants were observed. Of 181 FNEs with blood cultures completed, 65 (36%) had pathogenic organism isolated. A total of 74 Gram negative and 18 Gram positive bacteria were isolated. Forty-eight (74%) FNEs had monomicrobial (MBSI) and 17 (26%) had polymicrobial (PBSI) bloodstream infections. Gram negative - Gram negative (10 out of 17, 59%) was the most frequent PBSI combination (Fig 1). Up to 75% (12 out of 16) of Gram-negative PBSI were MDR. The most common organism isolated was E. coli (38% of isolates). Participants with PBSI had higher early mortality rates at 7 days compared to MBSI and negative cultures (44%, 22%, and 16% for PBSI, MBSI, and negative respectively; HR (95% CI): 3.63 (1.49, 8.86) for PBSI v. negative/MBSI cultures). Similarly, PBSI was associated with higher mortality within 30 days of FNE onset (63%, 52%, and 38% for PBSI, MBSI, and negative respectively; HR (95% CI): 2.17 (1.09, 4.32) for PBSI v. negative/MBSI) (Fig 2). Figure 1. Bar graph showing combinations for polymicrobial bloodstream infections (PBSI). GNGN: Gram-negative – Gram-negative; GNGP: Gram-negative – Gram-positive; GNO: Gram-negative – Other (fungi); GPGP: Gram-positive – Gram-positive Figure 2. Kaplan-Meier failure curves of participants with negative cultures, monomicrobial infections and polymicrobial infections Conclusion: PBSI episodes were more likely to be multidrug resistant and are associated with higher mortality. Empirical therapy for patients with PBSI should consider multidrug resistant Gram-negative bacteria Disclosures: All Authors : No reported disclosures